Suprasellar Desmoplastic Infantile Astrocytoma: A Rare Case Report - Shobini Vishali VM; Neelayadakshi B; Vimal Chander R (Dr. Annil Mahajan, 2024)
Desmoplastic infantile astrocytoma (DIA) is a rare primary brain tumour representing 0.4% of all brain tumours and 1.25% of intracranial tumors in children. Here we present a case of 1-year-old child with complaints of irritability for 3 months and recurrent vomiting on food intake for 2 months. MRI showed a large suprasellar mass showing T1-hypointensity, T2/FLAIR-hyperintensity and intense enhancement postcontrast administration. The patient underwent frontal craniotomy and excision of the space occupying lesion. Histological examination revealed DIA, immunopositive for Glial Fibrillary Acidic Protein (GFAP). Here we present this case due to its rarity.